2007
DOI: 10.1542/peds.2006-1939
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Birth Outcome Among Mothers With Low Serum Cholesterol

Abstract: Total serum cholesterol <10th population percentile was strongly associated with preterm delivery among otherwise low-risk white mothers in this pilot study population. Term infants of mothers with low total cholesterol weighed less than control infants among both racial groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
5
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 78 publications
(86 reference statements)
6
100
5
3
Order By: Relevance
“…One concern regarding the potential use of very low-fat diets in women without hyperlipidemic syndromes is whether there would be any adverse effect on fetal brain development. A previous observational study has reported the association of very low (,10th centile) maternal total cholesterol with increased rates of microcephaly (25).…”
Section: Diet and Exercisementioning
confidence: 95%
See 1 more Smart Citation
“…One concern regarding the potential use of very low-fat diets in women without hyperlipidemic syndromes is whether there would be any adverse effect on fetal brain development. A previous observational study has reported the association of very low (,10th centile) maternal total cholesterol with increased rates of microcephaly (25).…”
Section: Diet and Exercisementioning
confidence: 95%
“…Low maternal HDL-C in early pregnancy has also been associated with increased risk of later GDM (23), and elevated HDL-C has been associated with lower rates of preterm birth (24). Both low (,10th centile) and high (.90th centile) maternal total cholesterol have been associated with preterm birth (6,25), with one study showing a trend to increased rates of microcephaly for low (,10th centile) maternal cholesterol (25) ( Table 2). Overall, there is good evidence that elevated triglycerides and low levels of HDL-C are associated with adverse maternal and neonatal outcomes for women without diabetes.…”
Section: Maternal Obesitymentioning
confidence: 99%
“…Recent association of low maternal serum cholesterol with preterm labor provides new support for this connection. 45 Nutrient-based treatments could be used in these targeted populations to prevent low birth weight or PTD, making further investigation of nutritional pathways key in the investigation of genetic predisposition to PTD.…”
Section: Future Studiesmentioning
confidence: 99%
“…It is thought that progressive increase in oestrogen levels during gestation induces most of these alterations in lipoprotein metabolism (Desoye et al, 1987), which suggests the necessity of these metabolic changes for pregnancy maintenance and foetal growth. Indeed, reduced maternal TC levels are associated with intrauterine growth restriction and preterm delivery (Sattar et al, 1999;Edison et al, 2007). Conversely, marked elevated maternal TC and TG levels are associated with an increased risk on pre-eclampsia and other pregnancy-related complications (vandenElzen et al, 1996;Enquobahrie et al, 2004).…”
Section: Introductionmentioning
confidence: 99%